2016
DOI: 10.1039/c6tb00710d
|View full text |Cite
|
Sign up to set email alerts
|

Partially PEGylated dendrimer-entrapped gold nanoparticles: a promising nanoplatform for highly efficient DNA and siRNA delivery

Abstract: Partially PEGylated dendrimer-entrapped gold nanoparticles can be used as a promising nanoplatform for highly efficient pDNA and siRNA delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 41 publications
0
70
0
Order By: Relevance
“…Due to their unique properties, GNP are used more and more in the biomedical field, especially for drug delivery, gene delivery, and thermal treatment of cancer . GNP are usually synthesized from HAuCl 4 , a gold salt that can be reduced by various methods, such as Brust or Turkevish ones.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique properties, GNP are used more and more in the biomedical field, especially for drug delivery, gene delivery, and thermal treatment of cancer . GNP are usually synthesized from HAuCl 4 , a gold salt that can be reduced by various methods, such as Brust or Turkevish ones.…”
Section: Introductionmentioning
confidence: 99%
“…Although the AuNP‐linked plasmid deoxyribonucleic acid (DNA) or short interfering ribonucleic acid (siRNA) had been proved to facilitate their intracellular delivery, recent endeavors revealed that the polymer–Au hybrid nanoparticles with biocompatible polymer modification could further improve the stability of AuNP gene carriers, reduce the toxicity of carrier, and enhance gene delivery efficiency, as exampled in Figure a . As a typical example, Shi and co‐workers designed generation 5 (G5) dendrimer‐entrapped AuNPs with partially surface modification by PEG, and achieved improved expression efficiency of Luc or enhanced green fluorescent protein (EGFP) plasmid DNA as well as enhanced silencing effect by delivering Bcl‐2 siRNA . By capping AuNPs with l ‐cysteine methyl ester hydrochloride‐modified PEG, Rahme et al synthesized highly stable polymer–Au hybrid NPs, thanks to PEGylation‐induced interaction inhibition with serum proteins to avoid aggregation or to protect gene degradation by nucleases, as shown in Figure b .…”
Section: Applicationmentioning
confidence: 99%
“…Several types of NPs, such as liposomes, polymers, dendrimers, metal (e.g., gold, silver, iron oxide), and carbon, have being developed for application in cancer therapeutics [10]. Interestingly, a combination of different NPs, dendrimer-entrapped gold nanoparticles were recently used as a nanoplatform to induce gene silencing of cancer cells [22,23]. …”
Section: Addressing Current Drawbacks In Gene Silencing Therapy—fomentioning
confidence: 99%
“…As described above, dendrimer-entrapped gold nanoparticles (Au DENPs) were successfully used as platform for the delivery of vascular endothelial growth factor ( VEGF ) or B-cell lymphoma/leukemia 2 protein ( BCL-2 ) siRNA into a human glioma cell line [22] or BCL-2 siRNA to a human cervical carcinoma cell line, for silencing of luciferase ( LUC ) reporter gene and enhanced green fluorescent protein ( EGFP ) gene [23]. Moreover, Cui et al investigated dendrimer-coated AuNRs for brcaa1-shRNA delivery into MCF7 cancer cells, which led to a successful silencing of breast cancer 1 ( BRCAA1 ) gene [44].…”
Section: Addressing Current Drawbacks In Gene Silencing Therapy—fomentioning
confidence: 99%